2007
DOI: 10.1007/s10832-007-9013-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of V2O5 addition on the phase-structure and dielectric properties of zinc titanate ceramics

Abstract: V 2 O 5 -doped zinc titanate ceramics (ZnTiO 3 ) were prepared by conventional mixed-oxide method combined with a semi-chemical processing. The effects of V 2 O 5 addition on the phase-structures and the dielectric properties of ZnTiO 3 ceramics were investigated. The results show the sintering temperature of zinc titanate ceramics could be lowered from 1,150 to 930°C by reducing the size of starting powders using a semi-chemical processing; and with adding V 2 O 5 addition, the densification temperature of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Liu et al investigated the effect of V 2 O 5 , B 2 O 3 , and tungsten doping on sintering and phase transition of zinc titanate ceramics. Jothimurugesan and Gangwal evaluated the coprecipitation of a series of transition metal oxides with zinc−titanum oxides as a means of lowering the regeneration temperature of zinc titanate from 650 °C . They found that a combination of a small weight percent of nickel and cobalt added to zinc titanate effectively reduced the regeneration temperature by at least 100 °C without impacting sorbent performance in subsequent cycles …”
Section: Sulfur Sorption Materialsmentioning
confidence: 99%
“…Liu et al investigated the effect of V 2 O 5 , B 2 O 3 , and tungsten doping on sintering and phase transition of zinc titanate ceramics. Jothimurugesan and Gangwal evaluated the coprecipitation of a series of transition metal oxides with zinc−titanum oxides as a means of lowering the regeneration temperature of zinc titanate from 650 °C . They found that a combination of a small weight percent of nickel and cobalt added to zinc titanate effectively reduced the regeneration temperature by at least 100 °C without impacting sorbent performance in subsequent cycles …”
Section: Sulfur Sorption Materialsmentioning
confidence: 99%
“…Because of its relatively low sintering temperature and good dielectric properties, ZnTiO 3 has been regarded as a good candidate for low-temperature cofired ceramics (LTCCs), by which some novel multilayer communication modules involving the integration of passive components can be applied. It is necessary to lower the sintering temperature of dielectric ceramics in order to cofire with low melting point and highly conductive inner electrodes, such as Ag, Cu and their alloys [5,6]. From an industrial perspective, ZnTiO 3 is an active catalyst, paint pigment and phosphor, owing to its good semiconducting and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Various synthesis methods were reported in the past decades, such as solid-state reaction method [9], sol-gel process [10][11][12], molten salt synthesis [13] and a semichemical route combined with vigorous microbeads milling [1,5]. Nevertheless, pure hexagonal ilmenite-type ZnTiO 3 is not so easy to be synthesized, because ZnTiO 3 decomposes into cubic spinel Zn 2 TiO 4 and rutile TiO 2 at 945 1C [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…So CVO addition helps to inhibit the exaggerated grain growth and improve morphology of ceramics samples. In our previous studies [5,16], V 2 O 5 were melted at about 680°C; moreover, ZnO has a eutectic reaction with Zn 3 V 2 O 8 at about 890°C and the V-rich liquid phase can wet and dissolve Zn, then the V-rich liquid phase accelerated the solution and precipitation process of grains, and effectively helped the grains to move easily. As a result, the exaggerated grains formed.…”
Section: Resultsmentioning
confidence: 98%